1990
DOI: 10.1007/bf01955427
|View full text |Cite
|
Sign up to set email alerts
|

Plasma lipid-bound sialic acid alterations in neoplastic diseases

Abstract: Plasma lipid-bound sialic acid (LSA) was assayed in normal volunteers, patients with non-malignant diseases, and a variety of cancer patients. Mean plasma LSA in 50 normal volunteers, 16 patients with non-malignant diseases, 54 breast cancer, 17 lung cancer, 15 colon cancer, 7 ovarian cancer, 5 prostate cancer, 4 leukemia, 4 gastrointestinal, 3 thyroid cancer, 3 pancreas cancer and 2 adrenal cancer patients were 17.7, 23.2, 58, 85, 56.7, 46.2, 56.7, 53.3, 31.1, 33.2 and 119.5 mg/dl, respectively. None of the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
2

Year Published

1992
1992
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 9 publications
1
7
0
2
Order By: Relevance
“…Neoplastic transformation of a variety of cell types is associated with changes in the composition of membrane glycoproteins (Dwivedi et al, 1990). Glycoproteins are complex proteins in which carbohydrates are linked covalently to asparagine or serine or threonine residues of polypeptides.…”
Section: Wwwafricanethnomedicinesnetmentioning
confidence: 99%
“…Neoplastic transformation of a variety of cell types is associated with changes in the composition of membrane glycoproteins (Dwivedi et al, 1990). Glycoproteins are complex proteins in which carbohydrates are linked covalently to asparagine or serine or threonine residues of polypeptides.…”
Section: Wwwafricanethnomedicinesnetmentioning
confidence: 99%
“…The sialic acid level in malign cell surface is related with metastasis (5). Many researchers determined that total and lipid bounded sialic acid levels increased in different cancer types (27,28). It is known that the sialic acid is necessary for cell adhesion and carries out the electrostatic impulse in thrombocyte, cancer cells and erythrocytes via the negative charge (29).…”
Section: Discussionmentioning
confidence: 99%
“…The assay may be of some value in assessing the stage and metastatic spread of the disease, since in most types of cancer (e.g. breast, colon, lung and prostate cancer) sensitivity and absolute val ues are higher in extensive disease and in patients with distant metastasis than in those with local disease [3,32,33,35,36,43], The assay may also be helpful in monitoring can cer therapy [29,32,33,37,38,40,46]. In tumor recurrence 'LASA' levels often increase before the appearance of clinical symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Using a homeostatic autoregressive time-series model, a statistically significant (p < 0.05) reference change of ±51 mg/l between two consecutive measurements was found in 88% of the healthy subjects. Munjal et al [52] found an interassay variation of less than 10% and an intraassay reproducibility of 14-16%, whereas Dwivedi et al [43] found an intraassay variation of 6%. A slight, but statistically significant increase in the mean 'LASA' concentration was found in smokers and ex-smokers, when compared to nonsmok ers [30,47], As with carcinoembryonic anti gen (CEA) this should be taken into account when using the plasma concentration of se rum 'LASA' as a cancer marker.…”
Section: Assay Methodsmentioning
confidence: 99%
See 1 more Smart Citation